Vegetation and carbon gas dynamics under a changed hydrological regime in central European peatlands - Urbanová, Zuzana (Jihočeská univerzita, 2012)
The effect of drainage and restoration on the ecology of different types of peatlands in the Šumava Mountains was investigated. The study was focused primarily vegetation dynamics, carbon gas fluxes and their linkages under the affected hydrological regimes.
Vegetation and carbon gas dynamics under a changed hydrological regime in central European peatlands
Keywords: peatland; drainage; restoration; CH4; CO2; carbon; fen; bog; peatland; drainage; restoration; CH4; CO2; carbon; fen; bog